Metapopulation dominance and genomic-island acquisition of Bradyrhizobium with superior catabolic capabilities - Hollowell, Amanda C. (Proc Biol Sci, 2016)
Root nodule-forming rhizobia exhibit a bipartite lifestyle, replicating in soil and also within plant cells where they fix nitrogen for legume hosts. Host control models posit that legume hosts act as a predominant selective force on rhizobia, but few studies have examined rhizobial fitness in natural populations. Here, we genotyped and phenotyped Bradyrhizobium isolates across more than 800 km of the native Acmispon strigosus host range. We sequenced chromosomal genes expressed under free-living conditions and accessory symbiosis loci expressed in planta and encoded on an integrated ‘symbiosis island’ (SI). We uncovered a massive clonal expansion restricted to the Bradyrhizobium chromosome, with a single chromosomal haplotype dominating populations, ranging more than 700 km, and acquiring 42 divergent SI haplotypes, none of which were spatially widespread. For focal genotypes, we quantified utilization of 190 sole-carbon sources relevant to soil fitness. Chromosomal haplotypes that were both widespread and dominant exhibited superior growth on diverse carbon sources, whereas these patterns were not mirrored among SI haplotypes. Abundance, spatial range and catabolic superiority of chromosomal, but not symbiosis genotypes suggests that fitness in the soil environment, rather than symbiosis with hosts, might be the key driver of Bradyrhizobium dominance.